MENINGKATKAN KEMAMPUAN BERHITUNG PADA MATERI OPERASI HITUNG BILANGAN MENGGUNAKAN METODE DRILL SISWA KELAS I SD NEGERI CIWALAT - Basuki Sumanegara, Kiki; Astri Sutisnawati; Lutfi Hamdani Maula (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Numeracy skills are fundamental competencies that elementary school students must master because they serve as the basis for learning mathematics. However, preliminary observations in Grade I of SD Negeri Ciwalat indicated that students’ numeracy skills in number operations were still low. Of the 33 students, only 15 students (45.45%) achieved the Minimum Mastery Criterion (MMC), with an average score of 59.09. This study aimed to improve students’ numeracy skills through the implementation of the drill method in number operations learning. The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 33 first-grade students, consisting of 17 boys and 16 girls. Data were collected through observation, tests, and documentation and analyzed using quantitative and qualitative techniques. The results showed that the drill method improved students’ numeracy skills. The average score increased from 59.09 in the pre-cycle stage to 67.58 in Cycle I and 77.88 in Cycle II. Learning mastery also increased from 45.45% in the pre-cycle stage to 60.61% in Cycle I and reached 78.79% in Cycle II. Therefore, the drill method was effective in improving students’ numeracy skills in number operations among first-grade students of SD Negeri Ciwalat.